Extending the Transdiagnostic Model of Attachment and Psychopathology - Ein-Dor, Tsachi; Viglin, Dina; Doron, Guy (Frontiers in Psychology, 2016)
Research has suggested that high levels of attachment insecurities that are formed through interactions with significant others are associated with a general vulnerability to mental disorders. In the present paper, we extend Ein-Dor and Doron's (2015) transdiagnostic model linking attachment orientations with internalizing and externalizing symptoms, to include thought disorder spectrum symptoms. Specifically, we speculate on the processes that mediate the linkage between attachment insecurities and psychosis and obsessive compulsive disorder (OCD) symptoms, and indicate the different contexts that might set a trajectory of one individual to one set of symptoms while another individual to a different set of symptoms.